Analysis of Ferritin Serum in Anemia Pregnant Woman - Irianti, Evi (Scientechno: Journal of Science and Technology, 2024)
Anemia remains a common comorbidity complicating over 28% of pregnancy in Indonesia by 2023, Iron deficiency anemia is the most common, and to date, ferritin serum has been used as a diagnostic marker, but has not been routinely examined in pregnant women, thus hindering the accurate diagnosis of iron deficiency anemia in pregnant women. Our study aimed to examine ferritin serum among pregnant women, as well as, to investigate the prevalence of iron deficiency anemia in the Dalu Sepuluh Health Center of Deli Serdang Regency. A total of 60 pregnant women were randomly selected to participate in this cross-sectional study. We found that iron deficiency anemia was most common in pregnant women aged 20 – 35 years old (75%), with second-trimester pregnancy (36.7%), multigravida, and multiparity. Interestingly, 57% of pregnant women were considered malnourished (upper arm circumference of < 23.5 cm) which was found in 36.7% of primigravida and is associated with moderate iron deficiency anemia (71.4%), marked with < 30µg/L ferritin serum (p < 0.05). Cut-off point of serum ferritin was 28.98 ng/dL with a sensitivity of 92% and a specificity of 91.4%, indicating that the body's iron levels are in low condition. This study indicated that lower levels of ferritin serum are associated with anemia in pregnant women. We suggested that ferritin serum be put as a mandatory routine examination in pregnancy.